Curahan Waktu Kerja Pemuda Pada Usahatani Jagung Di Desa Tompasobaru Satu Kecamatan Tompasobaru Kabupaten Minahasa Selatan - Siwu, Anggi Andre; Benu, Noortje Marsellanie; Porajouw, Oktavianus (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2024)
The objective of this research is to determine the extent of work hour allocation by youth in corn farming in Tompasobaru Satu Village. The data analysis method used is quantitative to calculate the Work Hours Allocation in corn farming. The data utilized in this research includes primary data and secondary data. The primary data is obtained through interviews using questionnaires, while the secondary data is obtained from journals and theses. The research results indicate that the work hour allocation by youth in corn farming is 7 hours per day for each process of activities as follows: 7 hours per day for land preparation, 7 hours per day for planting, 3 to 6 hours per day for weeding, 7 hours per day for fertilization, 7 hours per day for pest and disease control, 7 hours per day for harvesting, 0 hours for husking, 3 to 5 hours per day for transportation, 7 hours per day for drying, 3 to 6 hours per day for sorting and grading, 7 hours per day for storage, and 1 hour per day for selling.